Chronic disease care integration into primary care services in sub-Saharan Africa: a 'best fit' framework synthesis and new conceptual model. Issue 3 (26th September 2022) - Harrison, Simon R; Jordan, Aileen M
Abstract : Objective: To examine the relevance of existing chronic care models to the integration of chronic disease care into primary care services in sub-Saharan Africa and determine whether additional context-specific model elements should be considered. Design: 'Best fit' framework synthesis comprising two systematic reviews. First systematic review of existing chronic care conceptual models with construction of a priori framework. Second systematic review of literature on integrated HIV and diabetes care at a primary care level in sub-Saharan Africa, with thematic analysis carried out against the a priori framework. New conceptual model constructed from a priori themes and new themes. Risk of bias of included studies was assessed using CASP and MMAT. Eligibility criteria: Conceptual models eligible for inclusion in construction of a priori framework if developed for a primary care context and described a framework for long-term management of chronic disease care. Articles eligible for inclusion in second systematic review described implementation and evaluation of an intervention or programme to integrate HIV and diabetes care into primary care services in SSA. Information sources: PubMed, Embase, CINAHL Plus, Global Health and Global Index Medicus databases searched in April 2020 and September 2022. Results: Two conceptual models of chronic disease care, comprising six themes, were used to develop the a priori framework. The systematic review of primary research identified 16 articles, within which all 6 of the a priori framework themes, along with 5 new themes: Improving patient access, stigma and confidentiality, patient-provider partnerships, task-shifting, and clinical mentoring. A new conceptual model was constructed from the a priori and new themes. Conclusion: The a priori framework themes confirm a need for co-ordinated, longitudinal chronic disease care integration into primary care services in sub-Saharan Africa. Analysis of the primary research suggests integrated care for HIV and diabetes at a primary care level is feasible and new themes identified a need for a contextualised chronic disease care model for sub-Saharan Africa.